System Monitoring Calibration Oil and Gas Equipment at the Cepu Oil and Gas PPSDM Instrumentation Workshop Using Java Netbeans - Muksan Junaidi; Nurul Saidah (JIIFKOM (Jurnal Ilmiah Informatika dan Komputer), 2022)
Information on calibration reports of oil and gas equipment at the Instrumentation Workshop at the Cepu Oil and Gas Human Resources Development Center (PPSDM Migas) is still not real time, and the filing of reports is still manual in a special cabinet. Often constrained in the process of searching for documents, and confusing information on repair status and recalibration schedule. The purpose of this study was to develop a Calibration Monitoring System for Oil and Gas Equipment at the Instrumentation Workshop at PPSDM Migas Cepu, to facilitate monitoring of the calibration process, search for data, reduce paper usage, and update information on equipment repair status. Research data from calibration reports in 2017 were 113 and in 2018 there were 79 reports. Using UML (Unified Modeling Language) modeling and Java Netbeans programming language. The results of the research are a monitoring system for equipment calibration at the Instrumentation workshop, and it has been tested functionally with blackbox testing, 97% successful in accordance with its function.